One approach to the assessment of the financial situation of SME in regions - Evgeny Vostokov (European Regional Science Association (ERSA), 2014)
The assessment of a financial position of SME has very much importance as for the analysis of current situation in a regional economy, as for modeling of their development by drawing up medium-term forecasts. Definition of SMEsituationsshall be done for separate sectors (from 15 to 45) of economy. It would be required to observe over several thousand enterprises for full-scale research of SME situations in large regional economy on the basis of traditional statistical methods. Such assessmentsare possible with high costs to the past and practically aren't applicable for forecasting. Therefore it was required creating approach which would allow defining SMEs situation in each of business spheres on the basis of rather small samples. The proposed technique of financial situation assessment for SMEs based on David Durant's approach to determination of financial solvency and creation of probabilistic distributions such indicators as profitability of business (ROTA), solvency (cover ratio) and debts (dependenceratio). Samples examinations showed that ROTA is submitted to normal distribution, cover and dependenceratios - to logarithmic normal distribution. Besides, itwasdefined dependences of distribution parameters from average values that allow apply them knowing only the sectorial average values. Samples examination was revealed that ROTA distribution was independent from cover and dependence ratios distributions. Two last distributions are dependent that forces to consider their joint distribution at creation of an integrated assessment of a financial condition.
Keywords: O16; 330; SME; financial analysis; regional economy; quantative methods; probality distribution; monitoring of situation in the economy